Nonspecific Hyperamylasemia: A Case Report - Wiederkehr, Julio Cesar; Wiederkehr, Barbara A; Wiederkehr, Henrique A; Carvalho, Caroline A (JOP. Journal of the Pancreas, 2013)
Context The elevation of serum amylase and lipase are generally associated with pancreatic diseases. However they can be associated with different pathologies unrelated with amylase and lipase. Case report This paper aims to report a case of a patient diagnosed with nonspecific hyperamylasemia and warn of this possibility in the differentiation of hyperamylasemia. Conclusion The correct diagnosis of silent hyperamylasemia is important in order to determine whether there is the risk of pancreatic disease or if we are just ahead of a benign hyperenzymemia. Image: Splenic vein venography.